2017
DOI: 10.1017/s0007114517000204
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic supplementation in lean patients with non-alcoholic fatty liver disease: a pilot, randomised, double-blind, placebo-controlled, clinical trial

Abstract: Although non-alcoholic fatty liver disease (NAFLD) is the leading aetiology of liver disorders in the world, there is no proven treatment for NAFLD patients with normal or low BMI. The aim of this study was to evaluate the efficacy of synbiotics supplementation in NAFLD patients with normal or low BMI. In this randomised, double-blind, placebo-controlled, clinical trial, fifty patients with NAFLD were assigned to take either a synbiotic supplement or a placebo capsule for 28 weeks. Both groups were advised to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
133
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 30 publications
7
133
1
6
Order By: Relevance
“…However, despite the abundance of clinical trials, several pharmacological treatments J Gastrointestin Liver Dis, March 2018 Vol. 27 No 1: 41-49 for NAFLD/NASH have been proposed, such as diabetes medications [6][7][8][9], lipid-lowering drugs [10], antioxidants [8,9], and anti-tumor necrosis factor (TNF)-α agents [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the abundance of clinical trials, several pharmacological treatments J Gastrointestin Liver Dis, March 2018 Vol. 27 No 1: 41-49 for NAFLD/NASH have been proposed, such as diabetes medications [6][7][8][9], lipid-lowering drugs [10], antioxidants [8,9], and anti-tumor necrosis factor (TNF)-α agents [11].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no approved treatment for NAFLD although health promotion strategies and lifestyle modifications are recommended as the primary steps in disease management (Emamat et al, ; Hekmatdoost et al, ; Mokhtari, Poustchi, Eslamparast, & Hekmatdoost, ; Noori, Jafari, & Hekmatdoost, ; Rahimlou, Ahmadnia, & Hekmatdoost, ; Rahimlou, Yari, Hekmatdoost, Alavian, & Keshavarz, ). Over the past few years, numerous studies have been conducted to find plant‐based biological compounds for treatment of NAFLD (Bahrami et al, ; Mofidi et al, ; Saadati et al, ). Black seed ( Nigella sativa ) is one of the plant‐based compounds with protecting effects on the liver, kidney, digestive system, nervous system, and cardiovascular system, as well as antiinflammatory and antimalignancy effects (Darand, Alavian, & Hekmatdoost, ).…”
Section: Introductionmentioning
confidence: 99%
“…compounds for treatment of NAFLD (Bahrami et al, 2019;Mofidi et al, 2017;Saadati et al, 2019). Black seed (Nigella sativa) is one of the plant-based compounds with protecting effects on the liver, kidney, digestive system, nervous system, and cardiovascular system, as well as antiinflammatory and antimalignancy effects (Darand, Alavian, & Hekmatdoost, 2018).…”
mentioning
confidence: 99%
“…Malaguarnera et al revealed that therapy with synbiotic ( B. longum and Fos) and lifestyle intervention in NASH patients produced much more improvement compared lifestyle intervention alone including reduction of serum TNFα, CRP, endotoxin and AST levels, improvement in HOMA-IR and extent of NASH activity index [142]. Synbiotic therapy also showed improvement in levels of fasting blood glucose, TG and inflammatory cytokines in NAFLD patients [143,144]. Therefore, symbiotic is one of the promising gut microbiotatargeted interventions on NAFLD prevention or therapy, nevertheless, the therapeutic efficacy needs further clinical validation.…”
Section: Gut Microbiota-targeted Therapy With Symbioticmentioning
confidence: 99%